2000
DOI: 10.1177/000348940010900504
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Autoimmune Inner Ear Disease: An Electrocochleographic and Histophysiologic Study

Abstract: Systemic immunization with swine inner ear antigens in complete Freund's adjuvant induces functional disturbances in the cochlea. Morphometric data indicate that an endolymphatic hydrops develops within 2 weeks. It diminishes 6 weeks after immunization. A progressive decrease in the compound action potential amplitude is observed from 2 to 6 weeks after immunization. Enhancement of the amplitude of the summating potential is present without a clear overall correlation to the presence of endolymphatic hydrops. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The results of the present study demonstrated no correlation between hearing deterioration and nerve deterioration, nor did the severity of hydrops predict nerve deterioration. Although hydrops did correlate with overall hearing loss, as shown by studies using ABR, 48,49 other reports using more near‐field physiological measures have shown no such correlation in the animal model 50,51 . This implies that hydrops itself may be an epiphenomenon of Meniere's disease.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The results of the present study demonstrated no correlation between hearing deterioration and nerve deterioration, nor did the severity of hydrops predict nerve deterioration. Although hydrops did correlate with overall hearing loss, as shown by studies using ABR, 48,49 other reports using more near‐field physiological measures have shown no such correlation in the animal model 50,51 . This implies that hydrops itself may be an epiphenomenon of Meniere's disease.…”
Section: Discussionmentioning
confidence: 92%
“…Although hydrops did correlate with overall hearing loss, as shown by studies using ABR, 48,49 other reports using more near-field physiological measures have shown no such correlation in the animal model. 50,51 This implies that hydrops itself may be an epiphenomenon of Meniere's disease. This is supported by human temporal bone studies in which ELH was found in patients who did not exhibit symptoms of Meniere's disease in their medical history and therefore had "asymptomatic endolymphatic hydrops."…”
Section: Discussionmentioning
confidence: 99%
“…From then on, the animal model has been widely used in experimental research on Ménière's disease. Other procedures such as cauterization of the distal portion of the endolymphatic sac with silver nitrate, introduction of cholera toxin into the inner ear and various techniques for the induction of inner ear autoimmune disease also produce both histologic hydrops and hearing loss [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with Meniere's symptoms also have a higher rate of systemic autoimmune disease compared to what is expected in normal population . In animal models, antigen challenge either in the inner ear or with inner ear antigens consistently results in endolymphatic hydrops …”
Section: Histopathologymentioning
confidence: 99%
“…28 In animal models, antigen challenge either in the inner ear or with inner ear antigens consistently results in endolymphatic hydrops. [29][30][31] The autoimmune process can result in direct destruction of inner ear structures. In Wegener's granulomatosis, vasculitis is observed in the cochlea, vestibule, and facial nerve.…”
Section: Histopathologymentioning
confidence: 99%